Władza nad martwą naturą. Cézanne Herberta - Adamowska, Joanna (Wydział Sztuki UR, 2018)
This article is an interpretation of Zbigniew Herbert’s poem Still Life, taking into account a lot of contexts, e. g. the references to Cézanne’s life, work and its reception present in the poem, Herbert’s other opinions on the artist’s work, as well as the earlier interpretations of the poem (by Roman Bobryk and Magdalena Sniedziewska). The author of the article shows how in the poem on Cézanne Herbert presents one of the major problems of his own work, i. e. the relations between art and transcendence, between the divine and the human.
Power over still life. Herbert’s Cézanne
Keywords: Paul Cézanne; Zbigniew Herbert; martwa natura; Bóg – Kreator; przyroda; sztuka; artysta; still life; God the Creator; nature; art; artist